Yield and quality of Mavuno grass forage and silage mixed with agro-industrial by-products - Godina-Rodríguez , Juan Eduardo; Garay-Martínez , Jonathan Raúl; Orzuna-Orzuna, José Felipe; Limas-Martínez, Andrés Gilberto; Quintanilla-Medina, Jairo Jeu; Joaquín-Cancino, Santiago (Ecosistemas y Recursos Agropecuarios, 2025)
The objective was to evaluate the yield and quality of forage and silage of Mavuno grass at different cutting intervals with the use of additives. Forage yield was evaluated at intervals of 3, 6 and 9 weeks of regrowth, with two additives (orange peel and molasses). The treatments were: 1) Mavuno grass; 2) Mavuno grass + orange peel; 3) Mavuno grass + molasses and 4) Mavuno grass + orange peel + molasses. Dry matter yield (kg ha-1) and nutritional value; content (g kg-1 DM) of crude protein, acid detergent fiber, neutral detergent fiber, lignin; silage quality variables: pH, brix degrees and percentage of dry matter of the forage, were determined by a randomized complete block design. The data were analyzed by analysis of variance and the Tukey test was applied for comparison of means (α = 0.05). When harvesting the forage at nine-week intervals, the dry matter yield was 50 and 45% higher than that obtained in the third and sixth weeks, while the protein content at three-week intervals was 14 and 25% higher than that obtained in the sixth and ninth weeks, respectively. The increase in the cutting interval induced a higher dry matter yield, however, the protein content decreased and the fiber and lignin values increased, while the addition of additives to the ensiled forage improved quality parameters such as protein, brix degrees and dry matter percentage.